The Effect of Audit Fees, Switching Auditors, Auditor Specialization, and Client Importance on Audit Quality - Saria, Amalia Mustika; Meini, Zumratul; Digdowiseiso , Kumba (INTERNATIONAL JOURNAL OF ECONOMICS, MANAGEMENT, BUSINESS, AND SOCIAL SCIENCE (IJEMBIS), 2023)
This study aims to examine the effect of audit fees, switching auditors, audit specialization, and client importance on audit quality in manufacturing companies in the consumer goods industry sector listed on the Indonesia Stock Exchange (IDX) in 2016-2020. Data analysis in this study used secondary data taken from manufacturing companies in the consumer goods industry sector. The sample used is obtained in the purposive sampling method, which means that sampling is carried out based on certain criteria. With the criteria set, the number of samples used was 21 companies with 105 observations during the 2016-2020 research period. This study used the help of the SPSS application program version 25 using multiple regression analysis methods. The results of this study seen with the t-test show that audit fees affect audit quality, switching auditors does not affect audit quality, audit specialization affects audit quality, and client importance does not affect audit quality in manufacturing companies in the consumer goods industry sector listed on the Indonesia Stock Exchange (IDX) in 2016-2020.